Can a Group-Based Hope Intervention Reduce the Anxiety Level of Female Inmates? - Maria Yoanita Bina; Megah Andriany; Nur Setiawati Dewi (Poltekkes Kemenkes Surakarta, 2025)
Background: The prevalence of anxiety disorders is significantly higher among female inmates, often leading to reduced quality of life and maladaptive behaviors. Existing non-pharmacological therapies demonstrate limitations in correctional settings, creating a need for specialized interventions. The objective of this study was to evaluate the effects of group-based hope interventions on anxiety levels among female inmates. Methods: This quasi-experimental study employed a pre-test and posttest design with a control group. A total of 56 participants (n=28 intervention, n=28 control) were selected using purposive sampling. The group-based intervention was delivered in 10 sessions, comprising four for group formation and six core sessions focused on goals, pathways, and agency. Anxiety levels were measured using the State Anxiety Inventory (STAI). Analysis utilized paired t-tests and independent t-tests. Results: The intervention group showed a substantial decrease in mean anxiety scores from 43.00±3.859 (pre-test) to 34.61 ± 4.400 (post test) (Mean different = 8.393; p < 0.001). The control group also exhibited a significant change, with a slight mean increase of 1.821 points (p < 0.001). The independent t-test confirmed that the anxiety reduction in the intervention group was substantially greater than that of the control group (Mean different –10.571; p < 0.001). Conclusion: Group-based hope intervention proved to be significantly effective in reducing anxiety levels in female prisoners compared to the control group. These findings support the implementation of this strategy as an evidence-based, practical mental health approach in correctional settings.